EMERGING FROM THE SHADOWS: IN THE COUNTRY OF LONGING AS A TESTIMONY TO LIFE - E, Rekha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present century has witnessed many tumultuous incidents in the history of mankind. The prospect of a third world war is a remote one, given the possibility of the usage of nuclear weapons. But, in many nations all over the world, a propensity for civil war or acute internal strife is gaining ground and they are being continually ambushed by the warring forces within their territories. The north African country of Sudan has been in great turmoil ever since clashes began in the region. The paper is an analysis of the power games that are oppressive tools which are utilized to dominate and maintain control over the population.